Innovative Approaches to Survey Research and Document Analysis in Contemporary Social Research - Moses Adeleke Adeoye (Universitas KH. Abdul Chalim Pacet Mojokerto, 2026)
Contemporary social research increasingly relies on survey research and document analysis, yet these methods face growing challenges arising from digitalisation, cultural diversity, data proliferation, and heightened ethical concerns. Traditional methodological frameworks, originally developed for more stable and homogeneous research contexts, are often ill-equipped to address issues such as declining response rates, interpretive bias, digital exclusion, and the epistemic implications of automated data processing. The purpose of this research is to critically examine survey research and document analysis in contemporary social research and to contribute conceptually to their methodological adaptation and innovation. Rather than generating original empirical data, the research adopts a conceptual and methodological research design grounded in critical-interpretive analysis. It draws on systematic critical engagement with existing methodological, theoretical, and interdisciplinary literature, employing conceptual synthesis and methodological critique as its primary analytical strategies. The findings reveal that many limitations associated with survey research and document analysis stem not only from technical constraints but from underlying epistemological assumptions embedded in standardisation, neutrality, and scale. The analysis further identifies emerging methodological innovations, such as adaptive survey design, AI-assisted document analysis, and reflexive ethical frameworks, as promising but requiring careful governance and contextual sensitivity. The research concludes that methodological renewal in social research must move beyond technical optimisation toward reflexive, inclusive, and ethically grounded approaches. By offering a structured conceptual framework and practical methodological guidance, this research advances methodological discourse and supports researchers in adapting established methods to complex contemporary research environments.